2009
DOI: 10.1182/blood-2008-09-177881
|View full text |Cite
|
Sign up to set email alerts
|

The BH3-only protein Bim plays a critical role in leukemia cell death triggered by concomitant inhibition of the PI3K/Akt and MEK/ERK1/2 pathways

Abstract: Mechanisms underlying apoptosis induced by concomitant interruption of the mitogen-activated protein kinase kinase/ extracellular signal-regulated kinase 1/2 (MEK/ERK1/2) and phosphatidylinositol 3-kinase (PI3K)/Akt pathways were investigated in human leukemia cells. Inhibition of these pathways using the MEK inhibitor PD184352 or U0126 and the PI3K/ Akt inhibitor perifosine strikingly induced apoptosis in multiple malignant human hematopoietic cells, and substantially reduced the colony-forming capacity of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 54 publications
(69 reference statements)
6
59
0
Order By: Relevance
“…Combined inhibition of both signaling pathways led to improved efficacy because of the enhanced induction of apoptosis, which can be in part attributed to the combined activation of pro-apoptotic BH3-only protein Bim as a result of MEK inhibition and repression of Mcl-1 as a result of PI3K/mTOR inhibition (35,39). Here, the ability of high Bim and low Mcl-1 expression to cooperatively initiate apoptosis in response to PI3K pathway and MEK inhibition is consistent with similar observations in human leukemia cells (40) and human lung cancer cell lines (41). In addition to exploring the effects of combining 2 targeted therapies, it is advantageous to exploit preclinical models to understand the effect of standard chemotherapies in combination with targeted therapeutics, given the established role of standard chemotherapy in ovarian cancer.…”
Section: Discussionsupporting
confidence: 75%
“…Combined inhibition of both signaling pathways led to improved efficacy because of the enhanced induction of apoptosis, which can be in part attributed to the combined activation of pro-apoptotic BH3-only protein Bim as a result of MEK inhibition and repression of Mcl-1 as a result of PI3K/mTOR inhibition (35,39). Here, the ability of high Bim and low Mcl-1 expression to cooperatively initiate apoptosis in response to PI3K pathway and MEK inhibition is consistent with similar observations in human leukemia cells (40) and human lung cancer cell lines (41). In addition to exploring the effects of combining 2 targeted therapies, it is advantageous to exploit preclinical models to understand the effect of standard chemotherapies in combination with targeted therapeutics, given the established role of standard chemotherapy in ovarian cancer.…”
Section: Discussionsupporting
confidence: 75%
“…combination with PI3K/AKT/mTOR agents, that Bim, along with other BH3 proteins, mediates the observed apoptotic response (43,52,53). Therefore the observations in our studies suggest that Bim may be contributing to the apoptotic response.…”
Section: Tc-305 (Krasmentioning
confidence: 48%
“…The induction of apoptosis when the MAPK and PI3K/AKT/ mTOR pathways are both inhibited has been frequently observed across a number of genetic subtypes (21,43,51). Furthermore, a number of in vitro studies have shown that increases in the proapoptotic protein Bim is observed following combination therapy (26,52). In our studies we wanted to evaluate this mechanistic observation in our in vivo models.…”
Section: Tc-305 (Krasmentioning
confidence: 99%
“…Furthermore, we showed that the combination of a PI3K inhibitor and a MEK inhibitor could function, at least in part, through a combinatorial effect on MTOR signaling, as has been demonstrated in other cell types (46). Other potential mechanisms could also explain the effectiveness of this powerful combination, including overlapping effects on the apoptosis machinery (51). The limitation for this combination approach in the clinic has been increased toxicity (52,53).…”
Section: Discussionmentioning
confidence: 99%